Murine SIGNR1 (CD209b) Contributes to the Clearance of Uropathogenic Escherichia coli During Urinary Tract Infections - Zhang, Yingmiao; Zhang, Song; He, Yingxia; Sun, Ziyong; Cai, Wentong; Lv, Yin; Jiang, Lingyu; Li, Qiao; Zhu, Sizhe; Li, Wenjin; Ye, Chenglin; Wu, Bicong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Uropathogenic Escherichia coli (UPEC), a Gram-negative bacterial pathogen, is a major causative agent of urinary tract infections (UTIs). However, the molecular mechanisms of how UPEC causes infections have not been determined. Recent studies indicated that certain enteric Gram-negative bacteria interact with and hijack innate immune receptors DC-SIGN (CD209a) and SIGNR1 (CD209b), often expressed by antigen-presenting cells (APCs), such as macrophages, leading to dissemination and infection. It was not known whether UPEC could utilize DC-SIGN receptors to promote its infection and dissemination similarly to the enteric pathogens. The results of this study reveal that UPEC interacts with CD209-expressing macrophages and transfectants. This interaction is inhibited by anti-CD209 antibody, indicating that CD209s are receptors for UPEC. Additionally, in contrast to the results of previous studies, mice lacking SIGNR1 are more susceptible to infection of this uropathogen, leading to prolonged bacterial persistence. Overall, the results of our study indicate that the innate immune receptor CD209s participate in the clearance of UPEC during UTIs.